2014
DOI: 10.3109/03639045.2014.956113
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and pharmacokinetics study on gastro-floating sustained-release tablets of troxipide

Abstract: The purpose of this research aimed at preparing gastro-floating sustained-release tablets of troxipide and a further study on in vitro release and in vivo bioavailability. Under the circumstances of direct powder compression, the floating tablets were successfully prepared with HPMC as main matrix material, Carbopol as assistant matrix material, octadecanol as floating agent and sodium bicarbonate as foaming agent to float by gas-forming. The floating time and accumulative release amount as evaluation indexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…More importantly, from the Concentration-time (C-t) curve the troxipide concentration in the GUGIG was slightly increased compared with that in the NCGIG, suggesting that troxipide was more easily absorbed into the blood of rats with GU than that of NC rats 41 . The T max of the GUGIG was not significantly different from that of the NCGIG, which suggested that the T max not related to dose and disease; this result is consistent with the findings of Gao's report 23 . The V z (0.069 ± 0.012, 0.061 ± 0.008, 0.064 ± 0.003 L/kg) of the GUGIG was significantly decreased (P < 0.01) compared with the V z (0.102 ± 0.015, 0.117 ± 0.024, 0.123 ± 0.02 L/kg) of the NCGIG, which suggested that the drug was more slowly distributed in GUGIG rats than in NCGIG rats.…”
Section: Pharmacokinetics and Tissue Distribution Study Methods Validsupporting
confidence: 91%
See 1 more Smart Citation
“…More importantly, from the Concentration-time (C-t) curve the troxipide concentration in the GUGIG was slightly increased compared with that in the NCGIG, suggesting that troxipide was more easily absorbed into the blood of rats with GU than that of NC rats 41 . The T max of the GUGIG was not significantly different from that of the NCGIG, which suggested that the T max not related to dose and disease; this result is consistent with the findings of Gao's report 23 . The V z (0.069 ± 0.012, 0.061 ± 0.008, 0.064 ± 0.003 L/kg) of the GUGIG was significantly decreased (P < 0.01) compared with the V z (0.102 ± 0.015, 0.117 ± 0.024, 0.123 ± 0.02 L/kg) of the NCGIG, which suggested that the drug was more slowly distributed in GUGIG rats than in NCGIG rats.…”
Section: Pharmacokinetics and Tissue Distribution Study Methods Validsupporting
confidence: 91%
“…Troxipide (3,4,5-trimethoxy-N-3-piperidinyl, Fig. 1 ), a defensive factor-enhancing therapeutic agent for gastritis and GU that exerts inhibitory, therapeutic and preventive effects to specifically those in the stomach by enhancing gastric mucosal blood flow and gastric mucosal defense factors and promoting tissue repair, blood circulation, metabolism and GU repair 23 25 . It is used to alleviate gastric mucosal lesions (erosion, hemorrhage, redness, and edema) in the acute gastritis and acute exacerbation stages of chronic gastritis.…”
Section: Introductionmentioning
confidence: 99%
“…Drug Dev Ind Pharm, Early Online:[1][2][3][4][5][6][7] Drug Dev Ind Pharm Downloaded from informahealthcare.com by Yale Dermatologic Surgery on 07/08/15For personal use only.…”
mentioning
confidence: 99%